Combating stress: the interplay between hormone signaling and autophagy in plants. (14th November 2019) - Liao, Ching-Yi; Bassham, Diane C
Abstract : This review summarizes recent findings on the relationship between autophagy and hormone signaling and metabolism in response to abiotic and biotic stresses. Abstract: Autophagy is a conserved recycling process in which cellular components are delivered to and degraded in the vacuole/lysosome for reuse. In plants, it assists in responding to dynamic environmental conditions and maintaining metabolite homeostasis under normal or stress conditions. Under stress, autophagy is activated to remove damaged components and to recycle nutrients for survival, and the energy sensor kinases target of rapamycin (TOR) and SNF-related kinase 1 (SnRK1) are key to this activation. Here, we discuss accumulating evidence that hormone signaling plays critical roles in regulating autophagy and plant stress responses, although the molecular mechanisms by which this occurs are often not clear. Several hormones have been shown to regulate TOR activity during stress, in turn controlling autophagy. Hormone signaling can also regulate autophagy gene expression, while, reciprocally, autophagy can regulate hormone synthesis and signaling pathways. We highlight how the interplay between major energy sensors, plant hormones, and autophagy under abiotic and biotic stress conditions can assist in plant stress tolerance.